2010
DOI: 10.1001/archsurg.2010.170
|View full text |Cite
|
Sign up to set email alerts
|

Using Complications Associated With Postmastectomy Radiation and Immediate Breast Reconstruction to Improve Surgical Decision Making

Abstract: Postmastectomy irradiation was associated with a high rate of surgical complications and implant loss among patients who underwent IBR. Determining the number of positive SLNs prior to definitive resection and reconstructive operations may reduce complications and implant loss by guiding surgical decision making. Patients with a negative SLN are unlikely to require PMRT. Those with positive SLN(s) are high-risk IBR candidates with a quantifiable PMRT risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Despite a lack of reported outcomes of a delayed-immediate approach to breast reconstruction [7,16,22,23] this approach is being used widely by more than 70% (105) of UK surgeons. This seems to be driven by the flexibility of being able to choose an appropriate second stage (autologous or implant based).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of reported outcomes of a delayed-immediate approach to breast reconstruction [7,16,22,23] this approach is being used widely by more than 70% (105) of UK surgeons. This seems to be driven by the flexibility of being able to choose an appropriate second stage (autologous or implant based).…”
Section: Discussionmentioning
confidence: 99%
“…This is beneficial as implant-based breast reconstruction in the setting of radiotherapy has been shown to have increased complications and reconstructive failures. [31][32][33][34] The initial use of a tissue expander also provides the patient with adequate time to evaluate all of her reconstructive options. Although not the focus of this article, we found that 15% of all patients desired a different final modality of breast reconstruction than originally planned.…”
Section: Discussionmentioning
confidence: 99%
“…The capsular contracture rate was similar for both groups (65). Retrospective data have shown that upfront staging sentinel lymph node biopsy may be useful in determining the probability of postmastectomy radiotherapy in clinically node-negative patients (66)(67)(68)(69)(70)(71). No randomized controlled trials have been conducted to compare upfront staging with intraoperative staging in the setting of immediate reconstruction.…”
Section: What Is the Appropriate Timing Of Breast Reconstruction?mentioning
confidence: 97%